Current perspectives in the USA on the diagnosis and treatment of pelvic inflammatory disease in adolescents - Risser, William L (Adolesc Health Med Ther, 2017)
In this review, the epidemiology, diagnosis, and treatment of pelvic inflammatory disease (PID) are discussed from a USA perspective and the difficulties that USA adolescents face in recognizing and seeking care for PID and other sexually transmitted infections (STIs) are emphasized. Females aged 15–24 years have the highest incidence of cervical infection with Chlamydia trachomatis and Neisseria gonorrheae, the principal causes of PID. PID is common in this age group. However, the incidence of PID in the USA is not known, because it is not a reportable disease, and because clinicians vary in the criteria used for the diagnosis. The Centers for Disease Control and Prevention (CDC) recommended the following diagnostic criteria that include lower abdominal or pelvic pain and at least one of the following: adnexal tenderness or cervical motion tenderness or uterine tenderness. Because PID can have serious sequelae, the criteria emphasize sensitivity (few false-negatives) at the expense of specificity (some false-positives). Patients who have PID are usually treated in the outpatient setting, following the CDC’s Guidelines for the Treatment of Sexually Transmitted Diseases 2015. They receive one dose of an intramuscular cephalosporin, together with 2 weeks of oral doxy cycline, and sometimes oral metronidazole. Improvement should usually be evident in 3 days. The USA does not offer comprehensive sex education for adolescents in public or private schools. Adolescents are unlikely to recognize the symptoms of PID and seek medical treatment. Confidentiality is important to adolescents, and low cost or free sources of confidential care are uncommon, making it unlikely that an adolescent would seek care even if she suspected an STI. The CDC has concluded that screening programs for chlamydia and gonorrhea infection help prevent PID; however, the lack of appropriate sources of care makes adolescents’ participation in screening programs unlikely.